PENGARUH PROBLEM SOLVING BERBANTUAN LEAD ADVERSITY QUOTIENT TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA SD - Erys Lilian Pertiwi; Lisa Virdinarti Putra (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aimed to determine the effect of using the Problem-Solving model assisted by LEAD Adversity Quotient on students' mathematical problem-solving abilities. The type of research conducted was quasi-experimental research. The sampling technique used was purposive sampling. The population of this study was all students of Bawen 01 Public Elementary School, and the sample selected for the research was the fourth-grade class of Bawen 01 Public Elementary School. Data were collected using test techniques (pretest, posttest) and non-test techniques (observation, documentation, questionnaire). The data analysis techniques included normality test, homogeneity test, simple linear regression test, and independent sample t-test. The research results revealed the following: (1) There was a significant difference between the control group and the experimental group in terms of mathematical problem-solving abilities, as evidenced by the significance level Sig. (2-tailed) of 0.019 < 0.05 using the independent sample t-test. (2) The implementation of the Problem-Solving model assisted by LEAD Adversity Quotient on students' mathematical problem-solving abilities was proven with a calculated t-value of 6.929 > t-table of 2.120 and a significance value of 0.000 < 0.05 using the simple linear regression test. In conclusion, the Problem-Solving model assisted by LEAD Adversity Quotient has a significant impact and difference in improving students' mathematical problem-solving abilities